Assessing age-related risks of gastrointestinal pathologies: a comparative study of gastroscopy outcomes across decades - Lac Nguyen; Noora Räsänen; Filippa Berggren; Michiel A. van Nieuwenhoven (Therapeutic Advances in Gastroenterology)
Background: Esophagogastroduodenoscopy (EGD) is the gold standard method for diagnosing upper gastrointestinal (GI) pathology. Swedish guidelines recommend patients over 50 years with new-onset dyspeptic symptoms undergo direct gastroscopy to rule out malignancy. However, the incidence of dysplasia or cancer in patients aged 61–70 years remains unclear. Objectives: To investigate the referral factors and endoscopic findings in patients aged 61–70 years and compare the result with age groups 51–60 and 41–50 years from our previous studies to establish whether there is an age cutoff for upper GI cancer risk. Design: A retrospective observational study was conducted to evaluate EGD referrals and outcomes in patients aged 61–70 years. Methods: We analyzed EGD referrals for patients aged 61–70 years within Region Örebro County from January 2019–April 2020 to January 2022–2023. Clinical data, including symptoms, medications, and laboratory results, were collected from medical records. Statistical analysis, including odds ratios (OR) and positive predictive values (PPV), was conducted to evaluate pathological outcomes based on referral factors. Results: A total of 1003 referrals were analyzed. Statistically significant differences in pathological findings were observed between the 41–50 years reference group and the older groups (51–60 years: OR 2.08, p  < 0.001; 61–70 years: OR 3.05, p  < 0.001). However, no statistically significant difference in cancer incidence was found between the age groups. Conclusion: The most common pathological findings were benign, including hiatal hernia, gastroesophageal reflux disease/esophagitis, or gastritis. The incidence of cancer was low in all three groups. These results suggest that the “test-and-treat” strategy, currently recommended for patients under 50 years, may be appropriate for patients aged 51–70 years as well. Trial registration: NCT04585516.